2019
DOI: 10.1108/pr-09-2017-0278
|View full text |Cite
|
Sign up to set email alerts
|

Social media snooping on job applicants

Abstract: Purpose The purpose of this paper is to investigate how HR professionals use social networking website information to evaluate applicants’ propensity to engage in counterproductive work behaviors and suitability for hire. Design/methodology/approach Using an experimental design, 354 HR professionals participated in a two-part study. In part 1, participants viewed a fictitious resume and rated the applicant’s likelihood to engage in counterproductive work behavior as well as likelihood of a hiring recommendat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 54 publications
3
26
0
3
Order By: Relevance
“…However, using SNWs, especially non-professional SNWs, and AI to screen and evaluate applicants is associated with many concerns, such as raising potential bias and discrimination issues among minority groups, evoking applicants privacy concerns when using their SNWs' information without consent, which in turn, can lead to legal and ethical challenges (Drouin, O'Connor, Schmidt, & Miller, 2015;Roth, Bobko, Van Iddekinge, & Thatcher, 2016;Van Iddekinge et al, 2016). Indeed, a recent study by Becton, Walker, Gilstrap, and Schwager (2019) showed that using applicants' information on their nonprofessional SNWs negatively influenced recruiter ratings of applicants, whereas no effects were found when using their information on professional SNWs. This questions the validity (job relevance), and reliability of such information, and further raise fairness and privacy concerns (Brown & Vaughn, 2011;Clark & Roberts, 2010).…”
Section: Privacy Concernsmentioning
confidence: 99%
“…However, using SNWs, especially non-professional SNWs, and AI to screen and evaluate applicants is associated with many concerns, such as raising potential bias and discrimination issues among minority groups, evoking applicants privacy concerns when using their SNWs' information without consent, which in turn, can lead to legal and ethical challenges (Drouin, O'Connor, Schmidt, & Miller, 2015;Roth, Bobko, Van Iddekinge, & Thatcher, 2016;Van Iddekinge et al, 2016). Indeed, a recent study by Becton, Walker, Gilstrap, and Schwager (2019) showed that using applicants' information on their nonprofessional SNWs negatively influenced recruiter ratings of applicants, whereas no effects were found when using their information on professional SNWs. This questions the validity (job relevance), and reliability of such information, and further raise fairness and privacy concerns (Brown & Vaughn, 2011;Clark & Roberts, 2010).…”
Section: Privacy Concernsmentioning
confidence: 99%
“…The findings of this study advance research in this area. Whereas past research has primarily focused on the effect that unprofessional posts (e.g., excessive comments and/or pictures related to alcohol consumption, the use of profanity, sexually explicit language, pictures, and/or references to sexual activity; Becton et al, 2019;Bohnert & Ross, 2010) have on an evaluator's perceptions of job applicants, this study focused on how social media posts about racism influence an evaluator's judgments of Black job applicants.…”
Section: Discussionmentioning
confidence: 99%
“…Although social media posts are primarily seen by people in an user's social network (e.g., Facebook friends, twitter followers), there are also situations in which an individual's social media profile and posts are seen by people outside their social network. In either case, what an individual chooses to post online has been shown to influence the perceptions that others have of them (Becton et al, 2019;Bohnert & Ross, 2010;Forest & Wood, 2012). For example, it is becoming increasingly common for human resource (HR) personnel and recruiters to use the information found on SNWs to help them determine whether to hire someone (Becton et al, 2019;Roth et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations